Species Delimitation of the Cycas segmentifida Complex (Cycadaceae) Resolved by Phylogenetic and Distance Analyses of Molecular Data - Feng, Xiuyan; Liu, Jian; Gong, Xun (Frontiers in Plant Science, 2016)
The Cycas segmentifida complex consists of eight species whose distributions overlap in a narrow region in Southwest China. These eight taxa are also morphologically similar and are difﬁcult to be distinguished. Consequently, their taxonomic status has been a matter of discussion in recent years. To study this species complex, we sequenced four plastid intergenic spacers (cpDNA), three nuclear genes and genotyped 12 microsatellites for the eight taxa from 19 different localities. DNA sequences were analyzed using Maximum Likelihood (ML) method and Bayesian Inference (BI), and microsatellites were analyzed using the Neighbor-joining (NJ) and structure inference methods. Results of cpDNA, nuclear gene GTP and microsatellites all rejected the hypotheses that this complex consisted of eight taxa or one distinct lineages (species) but two previously described species were adopted: Cycas guizhouensis K. M. Lan et R. F. Zou and Cycas segmentifida D. Y. Wang et C. Y. Deng. Cycas longlinensis H. T. Chang et Y. C. Zhong was included in C. guizhouensis and the other five taxa were included in C. segmentifida. Our species delimitation inferred from molecular data largely corresponds to morphological differentiation. However, the other two nuclear genes were unable to resolve species boundaries for this complex independently. This study offered evidences from different genomes for dealing with the species boundaries and taxonomical treatment of the C. segmentifida complex in an integrated perspective.